The characteristics of HIV-1 subtype B on phylogenetic dynamic and molecular transmission network in Fuyang City, China, 2011 to 2019 - Pan, Wenting; Gao, Nannan; Hu, Bing; Yin, Yueqi; Shen, Yuelan; Yang, Xiaohui; Wei, Wei; Ni, Jie; Dai, Seying; Miao, Lifeng; Qin, Yizu; Jin, Lin; et al. (Frontiers in Public Health, 2023)
HIV-1 subtype B, as once one of the earliest strains introduced into mainland China, rapidly spread in commercial plasma donors and heterosexuals in 1990s. To investigate the origin and evolutionary history of HIV-1 subtype B, we collected sequences tested from Fuyang in the east of China where higher prevalence of HIV-1 among commercial plasma donors and heterosexuals to construct a phylogenetic tree using the Markov chain Monte Carlo (MCMC) algorithm, infer molecular transmission network using TN93 model and visualize it with Cytoscape software. Our results showed that >99% of subtype B sequences belonged to Thai B. The sequences from Fuyang often cluster closer to those from other its adjacent cities. Which clustered together and formed a monophyletic cluster. HIV-1 B circulating in Fuyang dates back to approximately 1990. Among the 1,473 sequences, 166 were clustered at a genetic distance of ≤1.5%, resulting in 73 clusters. The degree of clustering with at least one other person was 11.27%. Among the transmission clusters, 50 (80.65%) comprised two individuals. Most clusters consisted of both heterosexual transmission routes and men who have sex with men. Phylogenetic and molecular network analyses revealed a common origin with neighboring regions in mainland China, local onwards transmission after its introduction, and a limited clustering degree. However, at least two co-existing transmission routes in most transmission clusters imply a greater challenge in controlling the spread of HIV-1. Our findings highlight the value on tailoring prevention interventions by combination of molecular surveillance and epidemiology.